National Lexicography Units: Past, Present, Future - Alberts, Mariëtta (Lexikos, 2011)
This article deals with the national dictionary offices of the previous bilingual dispensation, the eleven official national dictionary offices in the present multilingual dispensation, and the future prospects of these offices. It discusses the past dispensation in terms of the need and reasons for the establishment of national dictionary offices, i.e. national lexicography units (NLUs). Attention is given to the prescripts of the National Lexicography Units Bill (1996) for the establishment of NLUs, as well as the transfer of these units from the Department of Arts, Culture, Science and Technology to the Pan South African Language Board. The restructuring of dictionary units that existed prior to the multilingual dispensation is considered, together with the establishment of new dictionary units for the official African languages. The present situation is dealt with by describing the status quo at the NLUs in terms of housing, administration, funding, management, training, computerisation, cooperation, production and the like. The article concludes with some questions and reservations about the future of the NLUs, followed by a number of apposite recommendations.